ANALISIS PENGARUH HARGA, LOKASI DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PADA KONVEKSI PADI COLLECTION - Agus Tri Santosa; Mamik M. Fuadi; Mohammad Irfan Taufiq (Cipasung Techno Pesantren: Jurnal Ilmiah, 2022)
Convection Padi Collection is engaged in the manufacture of mukena and Muslim clothing. The opportunity that convection has is quite large, but the lack of product availability in terms of the supply of fabric, yarn, and completeness of equipment affects the interest in purchasing convection Padi Collection products. Many factors influence purchasing decisions, some of which are price, location, and product quality. So, the authors analyzed the effect of price, location, and product quality on purchasing decisions on rice collection with multiple linear regression methods. The result of the study can be concluded that the constant is 44,377, meaning that the consistent value of the participation variable is 44,377, the price regression coefficient (X1) is 0.583, the location is 0.483 (X2) and product quality is 0.823 (X3) then the participation value increases by 0.583 for X1, while X2 is 0.483 and X3 is 0.823.